2010
DOI: 10.1002/cncr.25580
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HER2 gene status in breast carcinomas with polysomy of chromosome 17

Abstract: BACKGROUND:The current study was performed to determine the impact of polysomy 17 on the interpretation of HER2 testing of invasive breast carcinomas using fluorescent in situ hybridization methods. Current American Society of Clinical Oncology/College of American Pathologists guidelines define HER2-positive tumors as those with >6 HER2 genes per nucleus or those with HER2/CEP17 (chromosome 17) ratio >2.2. These guidelines are potentially contradictory in tumors with polysomy of chromosome 17. METHODS: Seventy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 30 publications
(40 reference statements)
3
42
0
1
Order By: Relevance
“…63 Single-nucleotide polymorphism karyotyping has also shown that true polysomy 17 is uncommon. 25 Collectively, these studies show that elevated CEP17 copy number is not a useful surrogate for polysomy 17 and that most cases previously assigned 'polysomic' status actually represent focal pericentromeric gains.…”
Section: Polysomy 17 and Response To Anti-her2 Therapymentioning
confidence: 95%
See 3 more Smart Citations
“…63 Single-nucleotide polymorphism karyotyping has also shown that true polysomy 17 is uncommon. 25 Collectively, these studies show that elevated CEP17 copy number is not a useful surrogate for polysomy 17 and that most cases previously assigned 'polysomic' status actually represent focal pericentromeric gains.…”
Section: Polysomy 17 and Response To Anti-her2 Therapymentioning
confidence: 95%
“…However, other studies have associated elevated CEP17 count ('polysomy'), particularly high CEP17 counts (CEP17 Z4), with IHC 3 þ staining. 25,47,52 In one series, 17 of 150 (9.8%) polysomic, HER2-nonamplified tumors showed positive (3 þ ) immunohistochemistry staining compared with 6 of 247 (1.5%) eusomic, HER2-nonamplified cases. 52 Others have found no evidence that elevated CEP17 count ('polysomy') contributes to HER2 overexpression.…”
Section: Polysomy 17 and Her2 Overexpressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, even the objectivity of FISH has been questioned. Abnormalities of chromosome 17 are frequent in breast cancer, and the measurement of ERBB2 gene status depends on the criteria used, a ratio of the ERBB2 copy number to the chromosome 17 centromere enumerating probe number (i.e., the HER2/CEP17 ratio) Ն2.0, a ratio Ն2.2, or a mean ERBB2 copy number Ն6.0; however, some tumors that show ERBB2 gene amplification according to an ERBB2 gene copy number Ͼ6 do not exhibit amplification according to the ERBB2/ CEP17 ratio (6 ). The rationale for assessing amplification status as a ratio to the centromeric region was to compensate for potential polysomy; however, detailed chromosomal analysis by comparative genomic hybridization and single-nucleotide polymorphism arrays have demonstrated that chromosome 17 polysomy is a rare event in breast cancer (7,8 ).…”
mentioning
confidence: 99%